Analisis Kelayakan Investasi Penambahan Gudang Bahan Baku Garam Beriodium Pada PT. SSD Lamongan - Subarkah, Septandro Triabi; Herlina, Herlina (Fakultas Teknik Universitas Tulang Bawang, 2024)
A warehouse is a place used to store finished goods or raw materials and is an important factor so that the production process runs optimally, therefore a company needs adequate facilities and infrastructure. PT. SSD Lamongan experiences limited storage space for raw materials in the form of krosok salt. This company wants to purchase raw materials in large quantities to avoid large increases in raw material prices in the dry, wet, and rainy seasons. However, the current warehouse capacity is insufficient to store these raw materials. So the company plans to build a new warehouse to store raw materials. The construction of this warehouse requires careful consideration and calculations so that it is profitable in the future. Therefore, the aim of this research is to analyze the feasibility of investment by considering market and financial aspects for 10 years, using the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) methods. Based on the results and calculations carried out by researchers, the Net Present Value (NPV) value obtained with an interest rate of 9.08% was IDR 4,615,037,364.00. The Internal Rate of Return (IRR) is 64.94% (IRR>9.08%) and the investment payback period (PP) will be returned for 1 year and 6 months. From the results obtained, this project is feasible. Keywords: Investment Feasibility, IRR, NPV, PP, Raw Material Warehouse